Breakfast with lolo - Flor, Steven
@Life is short. Breakfast with Lolo shows how a grandson ultimately lives life to the fullest with his grandfather as they go on an adventure in search of the most delicious pancakes for breakfast. This story is based on one of the most memorable experiences Steven Flor had with his grandfather before he passed away. And this short film depicts that special bond between them" -- https://www.imdb.com/title/tt1666585/plotsummary?ref_=tt_stry_pl